2015
DOI: 10.1002/alr.21654
|View full text |Cite
|
Sign up to set email alerts
|

Allergic rhinitis and associated risk of migraine among children: a nationwide population‐based cohort study

Abstract: Children with AR had a higher incidence and subsequent risk of migraine. Physicians should be more aware of migraine in children with AR who complain of headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
0
13
1
Order By: Relevance
“…In a univariate analysis, we also found a negative association between allergic rhinitis or conjunctivitis and migraine. This is inconsistent with previous studies that found a positive association in adults or children . Previous studies in children presented methodological limitations that may have biased the conclusions, in particular variability in the diagnosis of allergic rhinitis and possible recall bias.…”
Section: Discussioncontrasting
confidence: 90%
“…In a univariate analysis, we also found a negative association between allergic rhinitis or conjunctivitis and migraine. This is inconsistent with previous studies that found a positive association in adults or children . Previous studies in children presented methodological limitations that may have biased the conclusions, in particular variability in the diagnosis of allergic rhinitis and possible recall bias.…”
Section: Discussioncontrasting
confidence: 90%
“…Several studies have correlated allergic rhinitis with migraine in childhood, pointing either to a prominent prevalence of the latter in patients with atopy 10 , or to a higher than expected frequency of allergic conditions in migraineurs 5,7-9 . The susceptibility for developing migraine in children suffering from allergic rhinitis was also suggested 11,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Although this relationship may be bidirectional, two longitudinal surveys from Taiwan have reported a higher risk of developing migraine in atopic children in comparison with nonatopic children, especially those with allergic rhinitis 11,12 , suggesting a role of the immune system in the manifestation of migraine. On the other hand, anti-asthmatic and anti-allergic therapies were associated with decreased risk of migraine in children and adolescents 8 .…”
mentioning
confidence: 99%
“…Finally, the present research only included adults. Children with allergic rhinitis have been found to have a higher incidence and subsequent risk of migraine 30 . The results from our exploratory investigation in adult migraine patients do not exclude the possibility of a major relationship in the pediatric population, which is not affected by the senility of the immune system, or the influence of sex hormones observed in adults, especially women.…”
Section: Discussionmentioning
confidence: 99%